2021
DOI: 10.1515/hmbci-2021-0012
|View full text |Cite
|
Sign up to set email alerts
|

Elevated levels of neopterin and pentraxin 3 in patients with rheumatoid arthritis

Abstract: Objectives As a systemic inflammatory disease, rheumatoid arthritis (RA) is the most common inflammatory arthritis in the population and there is no specific diagnostic marker in laboratory tests. The purpose of the study was to determine whether serum neopterin and pentraxin 3 (PTX3) levels may be a marker of increased inflammation in RA patients. Materials and methods The study were consist of 30 RA patients and 30 healthy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Thirty studies (34 study groups) reported serum or plasma neopterin concentrations in a total of 2,618 RD patients (mean age 43 years, 32% males) and 5,318 healthy controls (mean age 42 years, 47% males) ( 55 , 59 , 61 , 64 67 , 69 – 87 , 89 , 90 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Thirty studies (34 study groups) reported serum or plasma neopterin concentrations in a total of 2,618 RD patients (mean age 43 years, 32% males) and 5,318 healthy controls (mean age 42 years, 47% males) ( 55 , 59 , 61 , 64 67 , 69 – 87 , 89 , 90 ).…”
Section: Resultsmentioning
confidence: 99%
“…Twenty studies were conducted in Asia ( 55 , 59 , 65 , 66 , 69 , 70 , 72 74 , 77 , 78 , 80 82 , 84 89 ), six in Europe ( 61 , 62 , 64 , 67 , 79 , 90 ), three in Africa ( 71 , 75 , 83 ), and the remaining one in America ( 76 ). Ten study groups included patients with RA ( 55 , 76 , 78 81 , 83 , 86 , 89 , 90 ), nine with SLE ( 55 , 65 , 70 , 71 , 75 77 , 82 , 84 ), eight with BD ( 59 , 65 , 66 , 69 , 72 74 , 87 ), three with IIM ( 62 , 88 ), two with pSS ( 64 , 67 ), one with SSc ( 61 ), and one with AS ( 85 ). The analytical methods used for measuring neopterin included an enzyme-linked immunosorbent assay (ELISA) in 18 studies ( 61 , 64 67 , 69 – 71 , 74 76 , 78 , 79 , 81 , 85 , 86 ,...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the cytokines involved in lesion progression, TNF is most closely associated with RA pathogenesis, and its antagonists have been successfully used to treat the disease [ 63 ]. The most important cytokines secreted by macrophages include TNF-α, IL-1α, IL-1β, IL-6, granulocyte-macrophage colony-stimulating factor (GM-CSF), CXC chemokines, macrophage inflammatory protein (MIP), monocyte chemoattractant protein (MCP), MMPs, and neopterin [ 64 , 65 , 66 ].…”
Section: Mesenchymal Stromal Cells and Macrophagesmentioning
confidence: 99%